PHYSICAL QUALITY TEST AND HEDONIC TEST OF PAPER SOAP PREPARATIONS FROM ETHANOL EXTRACT OF KENIKIR (Cosmos caudatus Kunth.) LEAVES WITH VARIATIONS IN GLYCERINE CONCENTRATION - Isna Atifah Rofiatin; Definingsih Yuliastuti; Pramita Yuli Pratiwi (Poltekkes Kemenkes Surakarta, 2025)
Soap is a cosmetic product that can kill bacteria that cause skin infections. Soap preparations can be innovated into paper hand-washing soap that is practical, hygienic, and effective in killing bacteria. A plasticizer, namely glycerin, influences the texture of paper soap. Glycerin in the formulation of paper hand-washing soap can weaken the hardness of the preparation and provide flexibility, resulting in thin soap-like paper. This research aimed to determine the effect of glycerin concentration on the physical and hedonic quality tests of paper hand-washing soap preparations. This research uses an experimental approach with a pre-experimental one-shot case study design. The results of the physical quality test of kenikir leaf ethanol extract paper soap with variations in glycerin concentration in the organoleptic test had a light yellow color, a grape fragrance, a stiff solid shape, elastic, and very elastic and homogeneous. The addition of variations in glycerin concentration affects the results of the physical quality assessment of water content and hedonic tests for texture. However, it does not affect the results of physical quality tests, pH, foam height, and hedonic tests for color and aroma of the preparation.